Transient modeling of a gas-liquid piston-cylinder mechanism for low temperature energy conversion applications - Ozcan, Hasan; Zamfirescu, Calin; Dincer, Ibrahim; Hariri, Sahar; Hariri, Ali Asghar (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2017)
Transient modeling of a novel piston-cylinder gas-to -liquid energy conversion mechanism is performed in order to estimate the isentropic efficiency and contribution of various losses to the total energy transfer of the mechanism. A ease study is performed to comparatively evaluate the contributions of losses. The cumulative efficiency of one cycle corresponds to 82.1% by considering heat transfer, clearance volume, friction, and valve losses. The energy of pressurized hydraulic fluid with high head can be used in high efficient hydraulic turbines, such as Pelton and Francis with efficiencies up to 93%, to produce electrical energy. The selection of these types of hydraulic machines lies under the motivation of having such a low volumetric flow rate and higher head pressures. The present integrated system efficiency offers promising results for power production from low-temperature thermal resources. (C) 2016 Elsevier Masson SAS. All rights reserved.
Keywords: Transient modeling; Piston-cylinder mechanism; Isentropic efficiency; Hydraulic turbines; CARBON-DIOXIDE CYCLE; EXPANSION DEVICE; POWER RECOVERY; EXPANDER; Thermodynamics; Engineering